Q&A with Brad Peters, Chairman and Founder, Birst - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
The man behind one of Silicon Valley’s leading Cloud Business Intelligence and Analytics firms shares his thoughts on the future of the data business